Short-Term Magnetic Field Variations From the Post-depositional Remanence of Lake Sediments - Nilsson, Andreas; Suttie, Neil; Hill, Mimi J. (Frontiers in Earth Science, 2018)
Palaeomagnetic records obtained from lake sediments provide important constraints on geomagnetic field behaviour. Secular variation recorded in sediments is used in global geomagnetic field models, particularly over longer timescales when archaeomagnetic data are sparse. In addition, by matching distinctive secular variation features, lake sediment palaeomagnetic records have proven useful for dating sediments on various time scales. If there is a delay between deposition of the sediment and acquisition of magnetic remanence (usually described as a post-depositional remanent magnetisation, pDRM) the magnetic signal is smoothed and offset in time. This so-called lock-in masks short-term field variations that are of key importance both for geomagnetic field reconstructions and in dating applications. Understanding the nature of lock-in is crucial if such models are to describe correctly the evolution of the field and for making meaningful correlations among records. An accurate age-depth model, accounting for changes in sedimentation rate, is a further prerequisite if high fidelity palaeomagnetic records are to be recovered. Here we present a new method, which takes advantage of the stratigraphic information of sedimentary data and existing geomagnetic field models, to account for both of these unknowns. We apply the new method to two sedimentary records from lakes Kälksjön and Gyltigesjön where 14C wiggle-match dating floating varve chronologies provide an independent test of the method. By using a reference magnetic field model built from thermoremanent magnetisation data, we are able to demonstrate clearly the effect of post-depositional lock-in and obtain an age-depth model consistent with other dating methods. The method has the potential to improve the resolution of sedimentary records of environmental proxies and to increase the fidelity of geomagnetic field models. Furthermore, it is an important step toward fully explaining the acquisition of post-depositional remanence, which is presently poorly understood.